Insuficiência renal aguda. Estudo do quadro clínico e prognóstico. - Barretti, Pasqual [UNESP]; Soares, V. A. (My University, 1996)
Acute renal failure (ARF) is a frequent complication in hospitalized patients, and is strongly related to increase of mortality. PURPOSE: To analyze the clinical outcome and the prognostic factors in hospital acquired AFR. METHOD: A prospective study was performed. Data from 200 patients with established ARF admitted during the period of January, 1987 and July, 1990 were collected. RESULTS: The incidence of ARF was 4.9/1000 admissions. Renal ischemia (50%) and nephrotoxic drugs (21%) were the main etiologic factors. The histologic study done in 43 patients showed: acute tubular necrosis (53%), tubular hydrophic degeneration (16%), glomerulopathies (16%) and other lesions (15%). Dialysis therapy was performed in 101 patients and the main indications were: uremia (67%), hypervolemia (22%) and hyperkalemia (9%). The mortality rate was 46.5% and the most important causes of death were: sepsis (38%), respiratory failure (19%) and multiple organs failure (11%). Treatment withdraw was the cause of death in 2 patients. Higher mortality was observed in oliguric patients (62.9%) than non-oliguric (34.5%) (p < 0.05) and in ischemic renal failure (56.7%) when compared to nephrotoxic renal failure (14.7%) (p < 0.05). This difference was maintained when the comparison was done only between dialyzed patients. CONCLUSION: As primary cause of death was not associated to the acute renal failure, we conclude that acute renal failure is an important marker of the gravity of the underlying disease and not the cause of death.
Acute renal failure. Clinical picture and prognosis
Keywords: acute kidney failure; adult; aged; female; human; male; middle aged; mortality; prognosis; prospective study; renal replacement therapy; Adult; Aged; Female; Humans; Kidney Failure, Acute; Male; Middle Aged; Prognosis; Prospective Studies; Renal Dialysis